Ribo-On and Ribo-Off tools using a self-cleaving ribozyme allow manipulation of endogenous gene expression in C. elegans - Jie Fang; Jie Wang; Yuzhi Wang; Xiaofan Liu; Baohui Chen; Wei Zou (Communications Biology, 2023)
Abstract Investigating gene function relies on the efficient manipulation of endogenous gene expression. Currently, a limited number of tools are available to robustly manipulate endogenous gene expression between “on” and “off” states. In this study, we insert a 63 bp coding sequence of T3H38 ribozyme into the 3’ untranslated region (UTR) of C. elegans endogenous genes using the CRISPR/Cas9 technology, which reduces the endogenous gene expression to a nearly undetectable level and generated loss-of-function phenotypes similar to that of the genetic null animals. To achieve conditional knockout, a cassette of loxP-flanked transcriptional termination signal and ribozyme is inserted into the 3’ UTR of endogenous genes, which eliminates gene expression spatially or temporally via the controllable expression of the Cre recombinase. Conditional endogenous gene turn-on can be achieved by either injecting morpholino, which blocks the ribozyme self-cleavage activity or using the Cre recombinase to remove the loxP-flanked ribozyme. Together, our results demonstrate that these ribozyme-based tools can efficiently manipulate endogenous gene expression both in space and time and expand the toolkit for studying the functions of endogenous genes.